2016
DOI: 10.3141/2580-04
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Geotextile-Reinforced Bases for Paved Roads

Abstract: Geotextiles have been widely promoted for pavement structure over the past 30 years. However, there is a lack of well-instrumented, full-scale experiments to investigate the effect of geotextile reinforcement on the pavement design. In this study, full-scale accelerated tests were conducted on eight lanes of pavement test sections. Six out of these eight sections had granular bases reinforced with different types of woven geotextiles. The reinforced base sections and the control sections (with unreinforced bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Both woven and non-woven geotextiles have been widely used for reinforcement and hydraulic applications in pavement design ( 17 ). The reinforcement action of the geotextile provides bearing to the repetitive axle loads and distributes them to the subgrade soil ( 21 ). Additionally, the geotextile layer acts as a separation between the coarse and fine materials, laterally restrains the layers, and provides a tensioned membrane effect under the pavement, which helps to improve the pavement performance under long-term traffic loads ( 22, 23 ).…”
mentioning
confidence: 99%
“…Both woven and non-woven geotextiles have been widely used for reinforcement and hydraulic applications in pavement design ( 17 ). The reinforcement action of the geotextile provides bearing to the repetitive axle loads and distributes them to the subgrade soil ( 21 ). Additionally, the geotextile layer acts as a separation between the coarse and fine materials, laterally restrains the layers, and provides a tensioned membrane effect under the pavement, which helps to improve the pavement performance under long-term traffic loads ( 22, 23 ).…”
mentioning
confidence: 99%
“…In the pavements field, many researchers believe that the reinforcement structure employed in asphalt mixture layers can effectively improve the mechanical performance of asphalt pavement (1)(2)(3)(4)(5)(6)(7). Geosynthetic materials in widespread use for pavement applications are geocells, geogrids, and geotextiles.…”
mentioning
confidence: 99%
“…Pasquini et al observed the performance of geogrid reinforced asphalt pavement, based on the results of a real-scale field trial, the interface shear test, and the flexural test ( 5 ). Saghebfar M et al analyzed the reinforcement effect of the geotextile on the pavement structure with full-scale experiments ( 7 ). However, geogrid and geotextile are both 2D structures, generally arranged at the bottom of the asphalt layer.…”
mentioning
confidence: 99%
“…AASHTO M-288 ( 2 ) defines the function of geotextiles in roadway applications as subsurface drainage (i.e., filtration), separation, stabilization, and enhancement (which combines all three functions). Several field studies have previously been conducted with woven geotextile placed in between subgrade and base course in pavement profiles ( 3 6 ). Some of these studies involved exhuming geotextiles after they had been in service for up to 12 years and others were primarily based on monitoring performance.…”
mentioning
confidence: 99%